2021
DOI: 10.3390/cells10102609
|View full text |Cite
|
Sign up to set email alerts
|

Pathological AT1R-B2R Protein Aggregation and Preeclampsia

Abstract: Preeclampsia is one of the most frequent and severe complications of pregnancy. Symptoms of preeclampsia usually occur after 20 weeks of pregnancy and include hypertension and kidney dysfunction with proteinuria. Up to now, delivery of the infant has been the most effective and life-saving treatment to alleviate symptoms of preeclampsia because a causative treatment does not exist, which could prolong a pregnancy complicated with preeclampsia. Preeclampsia is a complex medical condition, which is attributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 144 publications
(388 reference statements)
0
4
0
4
Order By: Relevance
“…AT 1 R with PAR1 ( 138 ), μOR ( 139 ), prostaglandin F2aR ( 140 ), ET B R ( 141 ), RXFP1 ( in vivo ( 142 , 143 )), ADRB2 ( 144 ), AT 2 R ( 145 ), CB 1 R ( 146 ), secretin receptor (SCTR, class B) ( 147 ), bradykinin B 2 R ( 148 );…”
Section: Implications For Receptor Oligomerization and Heteromer Arra...mentioning
confidence: 99%
“…AT 1 R with PAR1 ( 138 ), μOR ( 139 ), prostaglandin F2aR ( 140 ), ET B R ( 141 ), RXFP1 ( in vivo ( 142 , 143 )), ADRB2 ( 144 ), AT 2 R ( 145 ), CB 1 R ( 146 ), secretin receptor (SCTR, class B) ( 147 ), bradykinin B 2 R ( 148 );…”
Section: Implications For Receptor Oligomerization and Heteromer Arra...mentioning
confidence: 99%
“…La incorporación de la aspirina (AAS) ha sido bastante debatida. Los datos primarios en el año 1985 mostraron la inicial prueba de que el AAS a bajas dosis alcanzaría aplazar los indicios de la preeclampsia, donde transitaron más de 30 años hasta que monumentales ensayos controlados con placebo consiguieron certificar la utilidad terapéutica de la aspirina para prevenir la enfermedad hipertensiva en embarazos de elevado riesgo (Quitterer & AbdAlla, 2021).…”
Section: Beneficiosunclassified
“…La aspirina inhibe la ciclooxigenasa (COX). Al disminuir el tromboxano (TXA2), modifica la relación PGI2/TXA2, reestableciéndose el balance fisiológico alterado por la invasión trofoblástica fallida (Quitterer & AbdAlla, 2021).…”
Section: Beneficiosunclassified
See 1 more Smart Citation
“…GPCRs are the key factors for the occurrence and development of major diseases, including cardiometabolic diseases ( Dorsam and Gutkind, 2007 ; Lappano and Maggiolini, 2011 ; Wang et al, 2018 ). Exploratory studies have revealed the essential functions of GPCRs in placental development and provided a sufficient theoretical basis that they can be used as potential targets for PE ( Conrad, 2016 ; McGuane and Conrad, 2012 ; Quitterer and AbdAlla, 2021 ). Based on the classification by structure and phylogeny analysis of GPCRs, Class B GPCRs, which are structurally characterized by large extracellular regions, contain the following two families, secretin GPCRs and adhesion GPCRs.…”
Section: Introductionmentioning
confidence: 99%